(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
An erosional unconformity has been recognized by means of lithostratigraphy and calcareous plankton biostratigraphy in the Cretaceous succession of the M. Misma area (Southern Alps, Lombardy Basin). Due to synsedimentary tectonism, after a Cenomanian sliding and slumping phase, channelized sandstones and conglomerates, of Late Turonian age, have been scoured in the Barremian-Albian succession.